Pengembangan Game 2D Pembelajaran Tentang Covid-19 Sebagai Media Pembelajaran Untuk Masyarakat Berbasis Android: Game 2D - meilany dewi; Anggy Trisnadoli; ibnu surya (Jurnal Komputer Terapan, 2022)
Covid-19 is an acronym for the English words â€œCorona Virus Disease â€“ 2019â€. The high growth of community mobile game users in Indonesia is quite large with the total number of mobile game players in Indonesia reaching 100 million in 2020. With the high growth of community mobile game users in Indonesia, alternative learning media in the form of games can be applied to appeal to the public about the dangers, modes of transmission and consequences of covid. This educational game was built as a learning medium for the public to be able to understand about covid-19, understand about covid-19, its consequences, how to spread it and how to prevent it. In this study, a survey was conducted to 30 respondents with quite diverse from various circles of students and students, entrepreneurs, employees, housewives and so on. The results of the study show that with this game, it can be an alternative to increase knowledge and understanding about COVID-19 as well as game-based learning media for the community. The entertainment provided by mobile-based learning games can be an interesting learning tool for the community.